(untitled) (Global Journal of Human-Social Science, 2024)
British Secretary of State for Digital Culture Media and Sport Nadine Dories proclaimed culture and sport the third front in the Ukrainian war Russia Ukraine but also national institutions in Western countries recognize this strong dimension in their own strategic conducts Music is clearly part of this War whether on the side of belligerents or of third party States cultural actors and artists even though they try to escape he dilemmas they cause What does mean listening music in such figuration Does it entail a bellephonic sound dissemination that could not be transcended or are there some experiments of musical diplomacies that tend to have another representation of otherness even in a context of war By focusing on several musical programs and institutions in Europe since the beginning of Ukraine War this paper aims at shedding light on the role of music as a source of recognition in strategic context from public diplomacy to people-to-people diplomacy